Time for an ASEAN digital currency? - Loh, Dylan Ming Hui (2020)
Countries around the world are increasingly alert to the potential social and financial benefits of Central Bank Digital Currencies (CBDCs), which are sovereign cryptocurrencies. ASEAN should start thinking of a regional-digital currency to stay ahead and deepen regional economic integration.